High-performance field emission device utilizing vertically aligned carbon nanotubes-based pillar architectures - Gupta, Bipin Kumar; Kedawat, Garima; Gangwar, Amit Kumar; Nagpal, Kanika; Kashyap, Pradeep Kumar; Srivastava, Shubhda; Singh, Satbir; Kumar, Pawan; Suryawanshi, Sachin R.; Seo, Deok Min; Tripathi, Prashant; More, Mahendra A.; et al. (AIP Advances, 2018)
The vertical aligned carbon nanotubes (CNTs)-based pillar architectures were created on laminated silicon oxide/silicon (SiO2/Si) wafer substrate at 775 degrees C by using water-assisted chemical vapor deposition under low pressure process condition. The lamination was carried out by aluminum (Al, 10.0 nm thickness) as a barrier layer and iron (Fe, 1.5 nm thickness) as a catalyst precursor layer sequentially on a silicon wafer substrate. Scanning electron microscope (SEM) images show that synthesized CNTs are vertically aligned and uniformly distributed with a high density. The CNTs have approximately 2-30 walls with an inner diameter of 3-8 nm. Raman spectrum analysis shows G-band at 1580 cm(-1) and D-band at 1340 cm(-1). The G-band is higher than D-band, which indicates that CNTs are highly graphitized. The field emission analysis of the CNTs revealed high field emission current density (4mA/cm(2) at 1.2V/mu m), low turn-on field (0.6 V/mu m) and field enhancement factor (6917) with better stability and longer lifetime. Emitter morphology resulting in improved promising field emission performances, which is a crucial factor for the fabrication of pillared shaped vertical aligned CNTs bundles as practical electron sources. (c) 2018 Author(s).